The Economic Impact of Trade Facilitation - Engman, Michael (OECD Trade Policy Papers, 2005)
This paper examines the economic impact of trade facilitation and in particular the link between trade facilitation and trade flows, government revenue and foreign direct investment. It is part of a series of studies that analyse various aspects of trade facilitation and the objective is to contribute to discussions in the WTO Negotiating Group on Trade Facilitation (NGTF) and elsewhere in the trade policy community. The paper finds that improved and simplified customs procedures would have a significant positive impact on trade flows. It further shows that a large number of mostly developing countries have managed to boost government revenue by implementing customs modernisation programmes that result in more efficient collection of trade taxes. In addition, the paper demonstrates that facilitated cross-border movement of goods would have a positive effect on the ability of a country to attract foreign direct investment and better integrate in international production supply chains